فعل الأمر في اللغتين العربية والجاوية (دراسة تقابلية) - Kuswoyo, Intan Handita; Efendi, Nasikul Mustofa (`A Jamiy : Jurnal Bahasa dan Sastra Arab, 2024)
Humans have the ability to receive and master several languages. Usually humans have the ability to master at least two languages, namely their mother tongue and a second language. Between the mother tongue and the second language there must be almost similar grammatical patterns or rules. Apart from that, there are also differences between the two. Languages in the world also have rules that are almost the same as each other. One of the rules that is often used to communicate is command words or imperatives which every language in the world definitely has with its own rules in each language. Therefore, this research was conducted to determine the differences and similarities between imperatives or command sentences in Arabic and Javanese, so that it can make it easier for Javanese speakers to learn Arabic, especially the rules of imperative sentences or command words. This research uses a literature study method with a focus on literature and sources in the form of books containing explanations of imperative sentences in Arabic and Javanese. The method and type of this research is qualitative research with a constructive analysis type of research which aims to (1) find out the similarities in imperative sentences in Arabic and Javanese (2) find out the differences in imperative sentences in Arabic and Javanese. The results of this research show that: (1) there are three similarities in imperative sentences in Arabic and Javanese, namely in terms of meaning, the same two meanings and sentence structure. (2) there are five differences in imperative sentences in Arabic and Javanese, namely in terms of meaning, signs, genderization, language level and in terms of number.